Elizabeth Fitzpatrick and James Kelly, eds.: Food and Drink in Ireland - Brears, Peter (Petits Propos Culinaires, 2017)
Elizabeth Fitzpatrick and James Kelly, eds.: Food and Drink in Ireland: Royal Irish Academy, 2016: 430pp., paperback, €25.00.